Mengeksplorasi Tweet Pariwisata Halal Indonesia di Media Sosial Menggunakan Pemodelan Topik dan Analisis Sentimen Berbasis Emosi - Putri Linggasari Sofi; Ratih Hendayani (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The purpose of this research is to explore halal tourism in Indonesia with the intention of knowing the topics discussed and knowing the sentiment of Indonesian people about halal tourism, this research uses topic modeling and sentiment analysis using the NRC Lexicon. The tweet data analyzed in this study are 13,746 tweets collected from 2014-2021 and have been cleaned. Topic modeling was formed into 7 topics and the findings of the sentiment analysis results stated that the sentiment of the Indonesian people was positive and believed in halal tourism in Indonesia. To respond to these findings, suggestions are given to business people, especially those in the tourism sector, to apply halal to their products. Then, the government must continue to encourage and develop halal tourism to become the best halal tourism destination in the world and also implement the halal supply chain to other sectors.